Corporate social responsibility and financial performance: exploring the relationship - Sandhu, H.S.; Kapoor, Shveta (2005)
Although there has been considerable research into the relationship between corporate social responsibility and financial performance, yet no real consensus exists as various studies revealed conflicting results reporting positive, negative or inconclusive relationship between the two. Based on the data set of 20 leading companies operating in India and covering a three-year period from 2000-01 to 2002-2003, this paper is an attempt to explore the association between corporate social responsibility and financial performance. The relationship is examined by using correlation and regression analysis which revealed no significant association between the variables under study. - Reproduced.
Keywords: Corporate governance